Choosing to Suffer: Reflections on an Enigma - Berger, Allan S. (Journal of religion and health, 2003)
Most people pursue pleasure and seek to avoid pain. Some individuals, however, choose a life characterized by pain and suffering. The author describes the most common varieties of such behavior patterns: asceticism, martyrdom, penance and masochism. Critical psychodynamics are discussed and the author proposes a synthesis of the motivation underlying pain/suffering seeking behavior.